Styl(e) poradnika. Wokół stylistycznego komponentu gatunku i tekstu - Ficek, Ewa (Stylistyka, 2019)
The aim of the present article was to conduct a primary analysis of a style/styles of a modern self-help manual (particularly in the form of a book), which analysis would take into consideration the following detailed problems: a handbook versus typical styles, the stylistic component of the handbook model, the style of a handbook and/versus the “handbook-like” style, the style of handbook texts. The observations presented here should be perceived as a fragment of a broader project which focused on recreating a model (a pattern) of the genre and its textual realisations. The analyses were conducted in line with the paradigms of linguistic genology and stylistics. The subject was selected on the basis of an assumption pertaining to the uncertain discursive status of handbooks – being now an expansive, polymorphic and transgressive form of discourse, which spreads its features to other genre forms. Uncertain remains the stylistic affiliation of this form of utterance, recognised by receivers/readers. Within the handbook sphere (no matter what genre it represents), one may introduce indicators of numerous styles and language variants. Specialist fields of science (law, Information Technology, medicine, etc.) impose their own, more or less hermetic ‘language’ on genre actualisations. Language styles are represented not only by verbal codes. In the case of handbooks, equally important is the image code – a picture, chart, or in a broader sense: a graphic shape of the text (a book). The review of textual empiricism should also be extended by stylistic distinctiveness which arises from individual preferences and traits of the author of discourse.